Development of a Manufacturing Industry Success Rate Analyzer Using Data Mining Technique - Mazlan, Eliza Mazmee (2010)
Starting up new businesses can be resource consuming. There are risks involved whenever new businesses are to be set up. This paper presents the development of a success rate analyzer to calculate the successful rate of setting up new manufacturing businesses particularly in Perak, Malaysia. Demographic data of Perak population is used and the data undergoes data mining process using the clustering technique and linear regression methods in analyzing the success rate of a manufacturing industry in Perak. With the result given by the application, new entrepreneurs can decide suitable location/district to set up the manufacturing business.